Plea Bargaining and Collateral Consequences: An Experimental Analysis - Malone, Carlie (2020)
The overwhelming majority of convictions in the United States are obtained through guilty pleas. Many of these guilty pleas are a product of plea bargaining, where a defendant enters a guilty plea in exchange for some form of official concessions. Despite its prominence, plea bargaining is subject to limited regulation. One consequence of this limited regulation is that courts generally only require the direct consequences of a guilty plea to be communicated to a defendant. Thus, when a defendant is deciding whether to plead guilty, he is often operating with incomplete information about the costly collateral consequences that may attach to a criminal conviction. The dominant theory of plea bargaining suggests that outcomes will largely mirror trial outcomes because bargaining occurs in the shadow of trial, but this may not be accurate if failure to communicate collateral consequences influences decisions to plead guilty. Using an experiment, this Note examines the extent to which communicating collateral consequences influences the decision to accept a plea bargain. Results from the experiment demonstrate that communicating collateral consequences decreases the rate of plea acceptance, but the effect of communication dissipates as the difference between the plea bargain sentence and the potential sentence at trial grows larger. Because communicating collateral consequences has an important effect on guilty pleas, this Note suggests that a lawyer’s failure to communicate such consequences to their client should be grounds for an ineffective assistance of counsel claim